2013
DOI: 10.1159/000351001
|View full text |Cite
|
Sign up to set email alerts
|

FGF23: A Mature Renal and Cardiovascular Risk Factor?

Abstract: High FGF23 predicts renal function loss in chronic kidney disease (CKD) patients and graft failure in transplant patients. FGF23, parathyroid hormone and serum phosphate are all interrelated but among these CKD-MBD biomarkers only FGF23 is independently related with CKD progression. High FGF23 associates with endothelial dysfunction in CKD patients and in elderly individuals in the general population. Furthermore, independently of serum phosphate, high FGF23 associates with mortality and left ventricular hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 81 publications
(68 reference statements)
0
15
0
Order By: Relevance
“…28 Of note, the increase in endothelium-dependent vasodilatation in our study occurred in the face of a doubling in plasma levels of FGF23, a biomarker that was associated to endothelial dysfunction in this population. 29 Observational studies in patients with CKD, like in the Chronic Renal Insufficiency Cohort (CRIC) study, 30 associated high FGF23 with adverse cardiovascular and renal outcomes. However, a recent meta-analysis 31 showed that in patients with CKD, paricalcitol is a safe drug with favorable effect on proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…28 Of note, the increase in endothelium-dependent vasodilatation in our study occurred in the face of a doubling in plasma levels of FGF23, a biomarker that was associated to endothelial dysfunction in this population. 29 Observational studies in patients with CKD, like in the Chronic Renal Insufficiency Cohort (CRIC) study, 30 associated high FGF23 with adverse cardiovascular and renal outcomes. However, a recent meta-analysis 31 showed that in patients with CKD, paricalcitol is a safe drug with favorable effect on proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…38 Although the current analyses adjusted for kidney function, FGF23 may be elevated prior to frank changes in the kidney. In addition, a positive association has been found between FGF23 and atherosclerosis, 39 though it is unclear whether it acts independently of phosphorus. 25,40 Finally, high circulating FGF23 has been associated with endothelial dysfunction and arterial wall stiffness, 4143 and inflammation 44,45 - factors which may contribute to the increased peripheral resistance typical of essential hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Several novel risk factors have been implicated in the elevated cardiovascular risk in CKD. Prominent non-traditional risk factors include red cell related measures such as anemia, iron status and red cell distribution width (RDW) [4], and markers of mineral metabolism, especially fibroblast growth factor 23 (FGF23) [5]. Interestingly, recent studies suggest a mechanistic link between these two systems [68].…”
Section: Introductionmentioning
confidence: 99%